2021
DOI: 10.1097/pec.0000000000002418
|View full text |Cite
|
Sign up to set email alerts
|

“Elbow-Lock” Chest Compression Method in the Setting of Single Rescuer Pediatric Cardiopulmonary Resuscitation

Abstract: Background: We designed a new 1-handed chest compression method, the "elbow-lock" chest compression (ELCC), for a single rescuer in pediatric cardiopulmonary resuscitation (CPR). Then, we compared the effectiveness between the ELCC and standard chest compression (SCC) method.Methods: This prospective, randomized controlled, crossover simulation trial studied 34 emergency medical professionals, including physicians, nurses, and EMTs. We compare the quality of chest compression and fatigue point time between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…Maintaining an appropriate joint ROM can reduce fatigue by minimizing muscle activity in the upper body, thereby enabling highquality chest compression [15]. When performing pediatric CPR, the use of the elbow-lock chest compression method, which involves rotating to allow the elbow to fix the direction of the hand, also enables the maintenance of an adequate chest compression depth and a high OCS [16]. The findings of this present study were consistent with those from previous studies, which showed that preventing elbow flexion is indeed effective in allowing high-quality chest compression [16].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining an appropriate joint ROM can reduce fatigue by minimizing muscle activity in the upper body, thereby enabling highquality chest compression [15]. When performing pediatric CPR, the use of the elbow-lock chest compression method, which involves rotating to allow the elbow to fix the direction of the hand, also enables the maintenance of an adequate chest compression depth and a high OCS [16]. The findings of this present study were consistent with those from previous studies, which showed that preventing elbow flexion is indeed effective in allowing high-quality chest compression [16].…”
Section: Discussionmentioning
confidence: 99%